Diskrimanasi Kelompok Liberal Terhadap Dakwah Orang Asli - Firdhausy Amelia; Zahrotunnimah Zahrotunnimah (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2019)
AbstractIn Malaysia, there are still a number of small minority groups living far from urban areas. They are called Orang Asli. The life system is still very simple and underdeveloped. This native place is often targeted by da'wah and other religious approaches each year. Until recently the emergence of a statement from the humanitarian group, namely Pro Human Rights (Proham), which refused to preach the native people. As well as criticizing the Universiti Kebangsaan Malaysia (UKM) for the involvement of indigenous propaganda. Then this issue received support from a group of liberals in Malaysia. They argue that these activities have usurped the right to freedom of religion. This statement shows that there are acts of discrimination against Islam. Because it is only addressed to the propaganda of Islam, does not offend and dispute other religions.Keywords: Liberals, Caucasians, Indigenous Peoples, Malaysia. AbstrakDi Negara Malaysia, masih ada sejumlah kelompok kecil minoritas yang hidup jauh dari perkotaan. Mereka ini disebut dengan Orang Asli. Sistem kehidupannya pun masih sangat sederhana dan terbelakang. Tempat orang asli ini sering dijadikan target dakwah dan pendekatan agama lain di setiap tahunnya. Hingga baru-baru ini munculnya pernyataan dari kelompok kemanusiaan, yaitu Pro Hak Asasi Manusia (Proham) yang menolak dakwah terhadap orang asli tersebut. Serta mengecam pihak Universiti Kebangsaan Malaysia (UKM) atas terlibatnya dakwah orang asli. Kemudian isu ini mendapat dukungan dari sekelompok orang liberal di Malaysia. Mereka berpendapat bahwa kegiatan tersebut telah merampas hak kebebasan beragama. Pernyataan yang dibuat ini menunjukkan adanya tindakan diskriminasi terhadap agama Islam. Karena hanya ditujukan kepada dakwah agama Islam, tidak menyinggung dan mempermasalahkan agama lainnya.Kata Kunci: Liberal, Dakwah, Orang Asli, Malaysia.